Are we ready to predict percutaneous nephrolithotomy (PCNL) stone-free failure?. (January 2016) - Gadzhiev, Nariman; Brovkin, Sergei; Grigoryev, Vladislav; Dmitriev, Vladimir; Baketin, Pyotr; Obidnyak, Vladimir; Pisarev, Aleksei; Shkarupa, Dmitry; Tagirov, Nair; Korol, Valeriy; Petrov, Sergei
Objective: To develop a tool, both simple and reliable, for postoperative percutaneous nephrolithotomy (PCNL) stone-free failure prediction. Materials and methods: We analysed a sample of 116 patients, who underwent conventional PCNL from 2011 to 2014. Cases with residual stones ⩽ 4 mm in size were regarded as clinically insignificant and 'stone-free'. Results: According to the low-dose computed tomography (CT) scan performed within 24 hours after operation, the patients were stratified as follows: 72 stone-free and 44 with residual stones. Among the analysed variables, three were derived as most important for prediction purposes: an additional stone in a calyx with an acute angle (⩽ 45°), represented by 'A'; an additional stone in a long calyx (⩾ 10 mm) with a narrow infundibulum (⩽ 8mm), represented by 'C'; and a stone size that is > 24 mm, represented by 'S'. These were abbreviated as the 'ACS' score. Depending on the absence or presence of each of these three variables, a score of 0 or 1 was assigned. If the ACS score is 0, then the probability of being a stone-free patient was about 88%; however, when the ACS score is 3, then the probability of being stone free was just 8%. Conclusion: Use of the ACS score seemed to be a simple and reliable tool for PCNL stone-free failure prediction.